Determining Optimal Capital Structure for PT Pupuk Kalimantan Timur (The Indonesian Journal of Business Administration, 2022)
PT Pupuk Kalimantan Timur (PT Pupuk Kaltim) is the largest Indonesian fertilizer producer. They wish to expand their business by building new plants. There are two ways to obtain external funding: debt and equity. The composition of debt and equity will affect the firm value. To maximize the firm value, optimal capital structure is needed to be estimated. Both qualitative and quantitative research methodology is used to analyze the optimal capital structure of the firm. This research use Library Research as a method for collecting data and secondary data are documentation of annual report, audited financial statement, data from credible website, and also media. The data period in this research is from 2013 to 2020. The optimal capital structure is calculated based on two approaches: cost of capital approach and APV approach.The result shows that the optimal capital structure based on cost of capital approach is 5%, while the current debt to capital ratio is 2.31%. The APV approach also shows that the current debt to capital ratio is lower than optimal debt ratio, which is 15% for all three scenarios: optimistic, most likely, and pessimistic. With the current condition of the firm that is underleveraged, the firm can take the new project with debt to increase the debt level and meet optimal capital structure that will increase the firm value. The current credit rating of PT Pupuk Kaltim is Aa2/AA, if the debt ratio is changed to 5% based on cost of capital ratio, the rating will decrease to A1/A+. While if it is changed based on APV approach with 15% debt ratio, it will decrease to A3/A- or Baa2/BBB, lower than cost of capital approach.Keywords: optimal capital structure, fertilizer producer, cost of capital approach, apv approach